Pendampingan Pengolahan Limbah Serabut Kelapa Menjadi Cocopeat dan Cocofiber dengan Mesin Pencacah di Desa Rejosari - Nurul Ratnawati; Agus Purnomo; Surya Desismansyah; Ferdinan Bashofi; Chania Ratu Iriana Putri (Jurnal Pemberdayaan Masyarakat, 2025)
This service activity focuses on utilizing the abundant coconut fiber waste in Rejosari Village by processing it into cocopeat and cocofiber using a shredding machine. Coconut fiber waste is often an environmental problem due to the accumulation and pollution it causes. The activity implementation method consists of three stages, namely (1) preparation, including coordination with the village and provision of tools; (2) implementation, which includes the introduction of coconut fiber shredding machine technology and how to process the waste into cocopeat and cocofiber which can be used as planting media and other materials that have economic value; and (3) follow-up, in the form of marketing assistance and product development. The results of the activity showed an increase in community understanding and skills in processing coconut fiber waste independently. Cocopeat produced can be used as an environmentally friendly planting medium, while cocofiber is used as a craft. This program provides economic benefits to the community and supports sustainable environmental management. In the future, the proposed follow-up includes optimizing marketing and developing coconut fiber-based derivative products.